Characterization of Air Voids and Permeability in Porous Asphalt Mixtures with Eggshell Ash as an Eco-Friendly Additive - Syammaun, Tamalkhani; Isya, Muhammad; Mahmud, Abdullah; Husaini (International Journal of Integrated Engineering, 2024)
Recently, there has been a lot of interest in the use of eco-friendly additives in asphalt mixtures in the field of pavement engineering. Such additives have been found to have the potential to enhance pavement performance while also mitigating the environmental impact of road construction. Eggshells are a restaurant waste product that is one of the additives that have been investigated in this study. The research aims to investigate the effect of eggshell ash (EA) on the air voids and permeability of porous asphalt mixtures. Two temperatures, 100°C (EA100) and 200°C (EA200), were used to prepare EA with varying percentages of 2%, 5%, 7%, 10% and 12% by weight of bitumen. The samples were then prepared and compacted by applying 50 blows on each side to measure air voids, and permeability testing was performed in the laboratories. The results indicated that the use of EA had impacted the permeability and air voids of the porous asphalt mixture. The amount of air voids in the mixes had a direct impact on the permeability coefficient, as the value of the permeability coefficient decreased with decreasing air voids. EA can serve as an additive to improve the permeability of asphalt mixtures, which may increase the pavement’s durability and longevity. Furthermore, the use of EA has the potential to reduce the environmental impact of the egg industry while improving the sustainability of road construction.